2019
DOI: 10.1186/s12883-019-1277-7
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous recession of a posterior cerebral artery aneurysm concurrent with carotid rete mirabile and moyamoya-pattern collateral vessels: a case report

Abstract: Background Carotid rete mirabile (RM) is a meshwork of multiple, freely intercommunicating arterioles that reconstitute the absent or hypoplastic segments of the internal carotid artery (ICA). Carotid RM has been reported to be associated with cerebrovascular diseases. However, it is rarely associated with moyamoya-pattern collateral vessels in the posterior cerebral artery (PCA) region and aneurysm. Case presentation A 39-year-old woman was admitted complaining of sudd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…By contrast, an aneurysm with rete mirabile is occasionally located in a unique site, which is difficult to approach, as in the current case and in some cases. 4 , 12) Even if an aneurysm can be approached, the current artery cannot be easily saved by direct clipping or coil embolization. Therefore, these treatments are not used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, an aneurysm with rete mirabile is occasionally located in a unique site, which is difficult to approach, as in the current case and in some cases. 4 , 12) Even if an aneurysm can be approached, the current artery cannot be easily saved by direct clipping or coil embolization. Therefore, these treatments are not used.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are some reports that the aneurysms located in collateral vessels could be disappeared by conservative therapy. 102 , 103) However, Kanamori et al 97) reported the importance of early surgical revascularization to prevent re-rupture of collateral artery aneurysms. Hence, we selected revascularization rather than conservative therapy for the present case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMD-associated collateral artery aneurysms are usually treated indirectly by surgical revascularization causing aneurysm obliteration due to an alteration of flow-related vessel dynamics [4,11,14,15,17,20]. The timing of bypass surgery after the initial bleeding remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In adult MMD, the combination of direct and indirect methods is beneficial as direct surgery can establish immediate blood flow, while indirect procedures can lead to a prolonged increase in perfusion [28,29]. In some patients, direct bypass can lead to spontaneous disappearance of the aneurysm in the collaterals [30]. Therefore, direct bypass plays a very important role in MMD treatment.…”
Section: (2) Bypass For Intracranial Ischemic Diseases (I) Moyamoya Diseasementioning
confidence: 99%